2004
DOI: 10.1158/1078-0432.ccr-03-0237
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurements of Capecitabine Metabolism in Bladder Tumors Overexpressing Thymidine Phosphorylase by Fluorine-19 Magnetic Resonance Spectroscopy

Abstract: Purpose: Previous studies have shown that tumor response to capecitabine strongly correlates with tumor thymidine phosphorylase (TP). The aims of our study were to (a) investigate the pharmacological role of TP by measuring the pharmacokinetics (PK) of capecitabine in a human bladder tumor model that was characterized by the overexpression of TP and (b) develop the use of PK measurements for capecitabine by fluorine-19 magnetic resonance spectroscopy as a noninvasive surrogate marker for determining TP levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…This study demonstrated the feasibility of using MRS to non-invasively monitor therapeutic transgene expression in tumors. Tumor response to capecitabine, a novel prodrug of 5-fluorouracil, strongly correlated with tumor thymidine phosphorylase expression levels in a transgenic human bladder tumor model, as monitored by using 19 F MRS of capecitabine as a surrogate marker for determining thymidine phosphorylase levels in tumor (101).…”
Section: Mrs Imaging Of Transgenic Cancer Modelsmentioning
confidence: 99%
“…This study demonstrated the feasibility of using MRS to non-invasively monitor therapeutic transgene expression in tumors. Tumor response to capecitabine, a novel prodrug of 5-fluorouracil, strongly correlated with tumor thymidine phosphorylase expression levels in a transgenic human bladder tumor model, as monitored by using 19 F MRS of capecitabine as a surrogate marker for determining thymidine phosphorylase levels in tumor (101).…”
Section: Mrs Imaging Of Transgenic Cancer Modelsmentioning
confidence: 99%
“…A detailed assignment of the 1 H/ 13 C/ 19 F and 15 N-NMR signals is presented in Table 3 . The form I of capecitabine should also be the one encountered in numerous studies on human liquids and organs [ 21 , 22 , 23 ] whose major content is water. At this stage of our studies, it should be mentioned that there is no reason to revise the notation of the capecitabine structure, as suggested previously [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most in vivo studies on MR pharmacokinetic measurements of tumors employ fluorinated drugs, such as [5- 19 F]-fluorouracil (5-FU) and its prodrug, as detected by 19 F MRS [88, 89], because 19 F MRS provides relatively high sensitivity combined with low background signal. Successful image-guided delivery of a prodrug enzyme, bacterial cytosine deaminase (bCD), which converts nontoxic [5- 19 F]-fluorocytosine (5-FC) to 5-FU, was recently reported in preclinical studies [90].…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%